Trauma assessment in outpatient psychotherapy and associations with psychotherapist's gender, own traumatic events, length of work experience, and theoretical orientation. Issue 1 (31st December 2022) - Lueders, Juliane; Sander, Christian; Leonhard, Anya; Schäfer, Ingo; Speerforck, Sven; Schomerus, Georg
ABSTRACT: Background: Traumatic events are strongly associated with mental health problems. At present, traumatic events and trauma-specific needs are commonly underdetected in therapeutic settings. Many mental health professionals lack key competencies for trauma inquiry and treatment. Objective: In this study, we aimed to investigate the everyday practices of dealing with traumatic events in outpatient psychotherapy in Germany as well as the influence of the therapist's gender, own traumatic events, length of professional experience, and theoretical orientation. Method: A total of 148 outpatient psychotherapists completed a purpose-designed online questionnaire. Therapists rated barriers and attitudes towards trauma assessment, possible requirements for enquiring about trauma, and practical aspects of trauma assessment. Results: Barriers reported in previous studies, e.g. fear of offending the patient or exacerbating their psychological state, could not be confirmed in our sample. Overall, participating therapists felt confident in engaging with traumatic events and considered enquiring about trauma important in all patients. Group differences were found for therapist's gender, own traumatic events, length of work experience, and theoretical orientation. Conclusions: Our results suggest that trauma training lowers barriers and raises therapists' self-confidence in dealing with patients´ traumatic experiences. Therapists' characteristics effecting trauma assessment should be considered during training. Due to the increasing demand for psychotherapy, especially considering people with severe mental illness affected by traumatic events, trauma training should be obligatory for all mental health professionals. HIGHLIGHTS: Barriers reported in previous studies were not confirmed in our sample of therapists with a high rate of specific trauma training. Group differences were found for therapist's gender, own traumatic events, length of work experience, and theoretical orientation.